Fire, livelihoods, and environmental change in the middle Mahakam peatlands, East Kalimantan - Chokkalingam, U.; Kurniawan, I.; Ruchiat, Y. (2005)
Large-scale, recurrent fires in Indonesia in recent decades have caused widespread deforestation and transformation of peatlands, and have contributed to substantial smoke haze and greenhouse-gas pollution. In some areas, local community use of fire for livelihood needs could be a major factor behind the widespread fires. The authors assessed fire patterns and their causes from the 1980s to the present in the Middle Mahakam peatlands of East Kalimantan. This was achieved through satellite image and GIS analysis, biological and social field surveys, and rapid rural appraisals in the villages. People living in or using the swamps employ fire annually along the waterways and adjacent open floodplains and forests, in conjunction with fishing, agriculture, and other livelihood activities. Local communities perceive that uncontrolled burning does not affect the fish, which is their economic mainstay. Dry and windy conditions, failure of regular livelihoods, new markets for turtles and tree bark, and easing of government quotas for these resources led to more widespread fires in the El Niño periods of 1982–1983 and 1997–1998. Repeated burning ultimately transforms larger and larger areas of peat forest into open floodplains and shallow lakes. Local communities promote the transformation, believing it enhances fishing conditions. Even if the interior forests were kept fire free for a lengthy period, they would likely not fully recover, but these areas were rendered highly fire prone during the last El Niño event in 1997–1998. Another long drought in the near future, coupled with widespread community burning, could cause more severe, long-lasting damage to the peat forests and contribute substantially to regional smoke haze and greenhouse-gas pollution. This paper discusses the scope for resolving the trade-offs between the communities’ perceived benefits of fire use, and national and global environmental concerns arising from peatland burning.